2015
DOI: 10.1007/s11694-015-9239-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesising a novel derivatives of piperine from black pepper (Piper nigrum L.)

Abstract: Black pepper (Piper nigrum L.) has gained a global consideration because of its volume in the spice industry. This plant has shown great potential for having medical applications and novel biologically active compounds. In black pepper, natural lipophilic amide piperine was isolated. Piperine was isolated from the fruit using glacial acetic acid as solvent. After isolation and characterization of piperine were done, then it is used to prepare new and novel derivatives of piperine through the experimental proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The peaks are more conspicuous in the OS‐pretreated sample than in control one, which suggests that in terms of retaining the structural bond integrity of the chili, OS‐pretreatment methods performed better. The FTIR spectra of the current work was analogous with the study conducted by Rodiles‐López et al (2020) and Aziz et al (2015) for chili sauce and black pepper ( Piper nigrum L.), respectively.…”
Section: Resultssupporting
confidence: 70%
“…The peaks are more conspicuous in the OS‐pretreated sample than in control one, which suggests that in terms of retaining the structural bond integrity of the chili, OS‐pretreatment methods performed better. The FTIR spectra of the current work was analogous with the study conducted by Rodiles‐López et al (2020) and Aziz et al (2015) for chili sauce and black pepper ( Piper nigrum L.), respectively.…”
Section: Resultssupporting
confidence: 70%
“…In traditional Ayurvedic medicine, P. nigrum is used in combination with P. longum to treat intermittent fevers, to promote the secretion of bile and recommended for neurological, broncho-pulmonary and gastrointestinal disorders, (including dyspepsia, flatulence, constipation and hemorrhoids) [140]. Moreover, Agbor et al [143] also reported on the folk medicine uses of fruits and leaves of P. nigrum for the treatment of coughs, intestinal diseases, bronchitis, venereal diseases, and rheumatism while Aziz et al [144] cited the general application of P. nigrum for treating diarrhea, fever, cold, colic disorder and gastric conditions.…”
Section: Traditional Uses Of Piper Speciesmentioning
confidence: 99%
“…The pattern of the spectra infers presence of flavonoid, phenolic and glycoside class of phytochemicals in the extract. [19,20] FTIR analysis of Curcuma longa powder . [22,23] FTIR Frequencies (IR max in cm…”
Section: Ftir Analysis Of Glycyrrhiza Glabra Root Aqueous Extractmentioning
confidence: 99%